Lobectomy in Patients with Cystic Fibrosis - Shahid I Sheikh; Karen McCoy; Nancy A Ryan-Wenger; Alpa Patel; Stephen Kirkby (Canadian Respiratory Journal)
BACKGROUND: Some patients with cystic fibrosis (CF) develop severe but localized lung disease or recurrent hemoptysis/pneumothorax refractory to conventional medical therapies.